Study on Starch Gelatinization Behaviors and Digestibility of Green Bananas during Microwave Drying - Yayuan XU; Suqing SHEN; Dajing LI; Jiangfeng SONG; Lei FENG; Zhuqing DAI; Zhongyuan ZHANG; Yadong XIAO (Shipin gongye ke-ji, 2022)
This study was aim to investigate the relationship between water migration and starch gelatinization behaviors of green bananas during microwave drying (MD) and its effect on starch digestibility. Taking green banana slices as the research object, different microwave power densities were designed to study the changes of microwave drying characteristics, starch gelatinization behavior and digestion characteristics for green bananas. The results showed that microwave power densities and drying time of MD showed a significant effect on the starch gelatinization behavior and digestion characteristics in green bananas. When the moisture content of banana was higher than 45%, a high microwave power density and high moisture content could promote the starch gelatinization in green bananas. While the moisture content was reduced to below 45%, the moisture content and microwave power density had no significant effect (P>0.05) on the degree of starch gelatinization. When the microwave power density was at the range of 2~8 W/g, there was a significant negative correlation (P<0.01) between RS content and the degree of starch gelatinization. And when the microwave power density was 2 W/g or 4 W/g, SDS content was significantly positively correlated with the degree of starch gelatinization (P<0.01), which indicated that a higher degree of starch gelatinization in green bananas could significantly promote the formation of SDS, and the highest SDS content could reach 53.90%. Therefore, the transformation from RS to RDS could be restrained through adjusting the microwave power densities and drying time to regulate the degree of starch gelatinization in green bananas, which could promote the formation of SDS, and reduce the content of RDS. This research could provide theoretical and scientific basis for microwave drying to efficiently retain resistant starch in green bananas or improve slow digestion starch.